Tasmania's child and family centres building parenting capability: a mixed methods study. Issue 14 (6th December 2019) - Jose, Kim; Christensen, Daniel; van de Lageweg, Wietse I.; Taylor, Cate
ABSTRACT: Tasmania's Child and Family Centres (Centres) provide a single entry point to early childhood services (ECS) and aim to improve the health and well-being, education and care of Tasmania's children through supporting families and carers. This mixed methods study investigated the impact of Centres on parents' confidence and competence. Centre users reported a slightly lower overall sense of parenting competence than non-users. There was no difference between Centre users and non-users in how they felt overall as a parent. Compared to non-Centre users, Centre users were more likely to report that ECS helped them develop new parenting skills. Centres supported parenting practices through a range of formal (i.e. parenting courses) and informal (i.e. role modelling) strategies. Centre users indicated that the combination of formal and informal parenting supports worked together to assist them build new parenting skills. The Centre model and partnership approach facilitates the development of positive parenting practices.